Pendidikan Entrepreneurship pada Lembaga Pendidikan Islam (Studi Kasus SMP Islam Terpadu Al-Imron) - Auril Putri Nabila; Jauharotul Makniyah (PT. Penerbit Tiga Mutiara, 2024)
Entrepreneurship Education at Islamic educational institutions (Case Study of Al-Imron Integrated Islamic Middle School). Judging from observations of Entrepreneurship education so far, there has been great attention to the existence of Entrepreneurship education in this school. Entrepreneurship education can be said to be the education of prospective entrepreneurs so that a person has self-confidence, courage, independence and skill so that they can minimize failure in a business. The aim of this research is how to implement Entrepreneurship education developed at Integrated Islamic Middle Schools and what problems are faced by Integrated Islamic Middle Schools; This research uses field research with a qualitative case study type approach; The research location was carried out at Al-Imron Integrated Islamic Middle School, Pekamban, Sumenep Regency; Informants for the implementation of this research were school principals, teachers and students; Data collection techniques are observation, interviews and documentation; The data analysis used is data reduction, data presentation and conclusions; The results of the research explain that there are two types of implementation of Entrepreneurship education developed at Integrated Islamic Middle Schools, namely the first formal type in the form of lesson plans and entrepreneurial practices by cultivating used goods and making food and drinks (herbal), the second non-formal type in the form of a bazaar. The problems faced by Integrated Islamic Middle Schools are limited study time and students lack of enthusiasm for Entrepreneurship education.